PERSEPSI MAHASISWA TERHADAP KEPEMIMPINAN PEREMPUAN PADA HMP SOSIOLOGI UNDANA STUDENTS’ PERCEPTIONS OF FEMALE LEADERSHIP IN THE SOCIOLOGY STUDENT ASSOCIATION - Maria Igniosa Ahoinnai; Chris S. Oiladang; Imanta I. Perangin Angin; Christine E. Meka (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: This study aims to examine students’ perceptions of female leadership in the Sociology Student Association (HMP) of the Faculty of Social and Political Sciences, Nusa Cendana University. The study was motivated by the phenomenon of female leadership, where women have consecutively held the position of Chairperson of the Sociology Student Association for five periods from 2021 to 2026. A qualitative method with a case study approach was employed. The study involved 14 active Sociology students from the 2022–2025 cohorts who were selected using purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using Attribution Theory. The findings reveal that students generally hold positive perceptions of female leadership. These perceptions are reflected in assessments of women leaders as communicative, empathetic, open to suggestions, disciplined, responsible, and capable of fostering harmonious relationships within the organization. Students also perceive female leadership as creating a participatory, inclusive, and supportive organizational environment that encourages member involvement. Nevertheless, female leaders continue to face challenges in the form of gender stereotypes, doubts regarding women’s leadership capacity, and the persistence of patriarchal cultural values. The study concludes that students’ perceptions of female leadership are predominantly positive and indicate a shift from gender-based evaluations toward assessments grounded in competence and leadership quality.Keywords: students’ perceptions, female leadership, student organization, attribution theory, gender equality.